Glocalization of Religious Extremism and Terrorism in Indonesia - Wahyudi; David Pradhan (Sospol : Jurnal Sosial Politik, 2021)
The rise of religious interpretation based political extremism culminating in violent terrorism is a serious threat confronting Indonesia in the 21st Century. The ostensibly multifarious and heterogenous impetus behind the origin of the resort to terrorism notwithstanding, the prevalent reductionist obscurantism surrounding the complexities underlying political violence justified through a religious referential, warrant academic re-interrogation, for deciphering the authenticity of the extant Western-dominated hypothetical paradigms. This theoretical, analytical Article, based exclusively on secondary sources, seeks to critically reinterpret the international and domestic factors that inspire terrorism in Indonesia. Drawing from the dominant theoretical explications and discourses accounting for the phenomenon of the proliferation of intermestic terrorism, the Article adopts a structural realist framework for interrogating the inductive effects of International politics on domestic terrorism in Indonesia.